Persepsi Siswa Tentang Kinerja Guru Terhadap Hasil Belajar Siswa pada Mata Pelajaran Administrasi Sistem Jaringan Kelas XI TKJ di SMKN 1 Rao Selatan - Syaputra, Dedy; Sesmiarni, Zulfani (Indonesian Research Journal on Education, 2022)
The purpose of this study was to determine how much influence the teacher's performance had on student learning outcomes in the subject of network system administration for class XI TKJ at SMKN 1 Rao Selatan. The population in this study were 131 students of SMKN 1 Rao Selatan. Respondents in this study were class XI TKJ1, TKJ2, TKJ3 and TKJ4. The sampling technique was cluster random sampling with random sample type. Cluster random sampling is a type of sampling technique in which a researcher divides the population into separate groups and takes several randomly selected samples. The type of research used is correlational. Types of research instruments with questionnaires or questionnaires and documents. Testing the data in this study using SPSS 22. The data were obtained through filling out questionnaires by students. The tests carried out are validity, reliability, normality, linearity, hypothesis testing and R square tests to determine how muchinfluence the teacher's performance has on student learning outcomes. From the research results, there is a significant positive effect between teacher performance and student learning outcomes. sign value. (2-tailed)each variable X and Y is < 0.05. Judging from the value of rcount > rtable, the rtable value is 0.355. While the results of the reliability test of the X variable have Cronbach's alpha > 0.06. The value of the X variable is 0.894 so it is said to be reliable. This shows that the instrument is a questionnaire that can be used to determine the effect of variable X. After processing, it is obtained R2 of 0.862, which means that the teacher's performance variable affects the variable student learning outcomes, giving an effect of 86.2%.